1994
DOI: 10.1017/s0252921100019734
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Structure of the Mon R2 Cloud Core

Abstract: High-resolution mm continuum observations are especially well suited to detect clumpy structures in molecular clouds. In this paper we concentrate on the Mon R2 cloud core which is associated with a cluster of IR sources. Walker et al. (1990) made a 1.3 mm map with 30″ resolution. They found an unresolved and elongated structure extending from NE to SW. Here, we discuss high-resolution continuum maps at 870 and 1300 µm showing a rich clumpy structure on the scale of several 10 arcsec. The clumps are probably i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 2 publications
1
47
0
Order By: Relevance
“…The UC Hii region has a cometary shape and its continuum peaks toward the infrared source Mon R2 IRS 1. Previous millimeter and farinfrared spectroscopic and continuum studies (Henning et al 1992;Giannakopoulou et al 1997;Tafalla et al 1997;Choi et al 2000;Rizzo et al 2003Rizzo et al , 2005Pilleri et al 2012Pilleri et al , 2013 showed that the molecular emission presents an arc-like structure surrounding the Hii region, with the bulk of the emission to the SW (see Fig. 1).…”
Section: Ultracompact Hii Region In Mon R2mentioning
confidence: 89%
“…The UC Hii region has a cometary shape and its continuum peaks toward the infrared source Mon R2 IRS 1. Previous millimeter and farinfrared spectroscopic and continuum studies (Henning et al 1992;Giannakopoulou et al 1997;Tafalla et al 1997;Choi et al 2000;Rizzo et al 2003Rizzo et al , 2005Pilleri et al 2012Pilleri et al , 2013 showed that the molecular emission presents an arc-like structure surrounding the Hii region, with the bulk of the emission to the SW (see Fig. 1).…”
Section: Ultracompact Hii Region In Mon R2mentioning
confidence: 89%
“…Palau et al (2011) Howard et al 1994;Carpenter et al 1997;Preibisch et al 2002). G213.70-12.6 hosts several infrared sources, the brightest of which is IRS 3 (L = 14 000 L ; Henning et al 1992). IRS 3 is a compact cluster of massive YSOs (Preibisch et al 2002) • ; Minier et al 2000).…”
Section: G17420-008mentioning
confidence: 99%
“…The central, spherical UC Hii was created by the interaction of the central infrared source IRS1 (Wood & Churchwell 1989) with its host molecular cloud. The formation of the B0V star associated with IRS1 created a huge bipolar outflow (∼15 = 3.6 pc long, Massi et al 1985;Henning et al 1992;Tafalla et al 1994). Later CO 3 → 2 mapping of the region showed that this very extended outflow is now inactive.…”
Section: Introductionmentioning
confidence: 98%